2022
DOI: 10.3390/biomedicines10102587
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity of Panduratin A against LPS-Induced Microglial Activation

Abstract: Uncontrolled and excessive microglial activation is known to contribute to inflammation-mediated neurodegeneration. Therefore, reducing neurotoxic microglial activation may serve as a new approach to preventing neurodegeneration. Here, we investigated the anti-inflammatory effects of panduratin A against microglial activation induced by lipopolysaccharides (LPS) in the SIMA9 microglial cell line. We initially examined the anti-inflammatory properties of panduratin A by measuring LPS-induced nitric oxide (NO) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The NF-κB signaling pathway is one of the general signal transduction pathways that mediate gene expression of proinflammatory and antiapoptotic factors, cell proliferation, differentiation, adhesion, migration and angiogenesis [ 14 ]. The hyperactivation of NF-κB signaling is a hallmark of many types of cancer [ 14 ] and inflammatory-associated pathologies [ 14 , 15 ]. Additionally, the chronic inflammation associated with upregulation of NF-κB signaling is a common feature of multiple neurodegenerative diseases [ 16 ].…”
Section: The Molecular Mechanisms Of Evp4593 Activitymentioning
confidence: 99%
“…The NF-κB signaling pathway is one of the general signal transduction pathways that mediate gene expression of proinflammatory and antiapoptotic factors, cell proliferation, differentiation, adhesion, migration and angiogenesis [ 14 ]. The hyperactivation of NF-κB signaling is a hallmark of many types of cancer [ 14 ] and inflammatory-associated pathologies [ 14 , 15 ]. Additionally, the chronic inflammation associated with upregulation of NF-κB signaling is a common feature of multiple neurodegenerative diseases [ 16 ].…”
Section: The Molecular Mechanisms Of Evp4593 Activitymentioning
confidence: 99%
“…Simultaneously, panduratin A increased the release of the anti-inflammatory cytokines IL-4 and IL-10, effectively attenuating the pro-inflammatory stage in neuroinflammatory diseases [19] , [20] . An in vitro study focused on the prevention of neuroinflammation-associated neurodegenerative diseases found that panduratin A counteracted lipopolysaccharide (LPS)-induced microglial activation in the spontaneous immortalized microglia-A9 (SIM-A9) cell line by reducing NO levels and pro-inflammatory cytokine production, and secretion [21] . Pinostrobin ( Fig.…”
Section: Introductionmentioning
confidence: 99%